Suggested functionalities of a software maintenance tool for a university application system. - Sulaiman, Hidayah; Abdullah, Rusli (International Journal of Computer Science and Network Security, 2008)
Using the right type of tool for maintenance activity and application support is essential in order to meet today's technological demands. These days, almost all business operations rely on application system efficiency. Maintenance is also seen as the highest percentage of work activity done in a software development life cycle as many software practitioners and researchers have quoted. Even in 1991 there was already a study by Abran et.al that showed a mere increased in the maintenance activity and support to users. This paper will present the result of a study done on various public and private universities of Klang Valley in Malaysia.